2018
DOI: 10.1080/02656736.2018.1507047
|View full text |Cite
|
Sign up to set email alerts
|

A network meta-analysis on the efficacy and prognosis of different interventional therapies for early-stage hepatocellular carcinoma

Abstract: View related articles View Crossmark data Citing articles: 2 View citing articles A network meta-analysis on the efficacy and prognosis of different interventional therapies for early-stage hepatocellular carcinoma

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Previous network meta-analyses have been performed, although their conclusions should be interpreted in an informed fashion. 18,19,78,79 Firstly, some previous NMAs included trials which evaluated patients beyond early stage HCC criteria (i.e. solitary HCC >5 cm or multifocal HCC >3 cm).…”
Section: Discussionmentioning
confidence: 99%
“…Previous network meta-analyses have been performed, although their conclusions should be interpreted in an informed fashion. 18,19,78,79 Firstly, some previous NMAs included trials which evaluated patients beyond early stage HCC criteria (i.e. solitary HCC >5 cm or multifocal HCC >3 cm).…”
Section: Discussionmentioning
confidence: 99%
“…A network meta-analysis by Lin et al [ 105 ] analyzed data in 5 RCTs and compared the efficacies of different interventional techniques for treatment of early stage hepatocellular carcinoma, including SR, RFA, MWA, PEI, CRA, laser ablation and external beam radiotherapy. However, in this previous meta-analysis, only RCTs were included, with some high-quality cohort studies being excluded.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, overall 5- and 10-year survival rates are similar to surgical resection, while there were large differences in local tumour control rates depending on the treatment strategy for insufficient ablative margin [44-49]. Most meta-analyses also demonstrated that ablation has similar OS but inferior local tumour control rates compared to resection [32, 46, 47]. However, two recent meta-analyses showed that resection had better recurrence-free and OS than RFA [32, 46].…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…Most meta-analyses also demonstrated that ablation has similar OS but inferior local tumour control rates compared to resection [32, 46, 47]. However, two recent meta-analyses showed that resection had better recurrence-free and OS than RFA [32, 46].…”
Section: Clinical Outcomesmentioning
confidence: 99%